Bioactive Eunicellin-Based Diterpenoids from the Soft Coral Cladiella krempfi - Chang-Feng Dai; Jyh-Horng Sheu; Ming-Shyan Huang; Zhi-Hong Wen; Chi-Jen Tai; Jui-Hsin Su (Marine Drugs, 2011)
Four new eunicellin-based diterpenoids, krempfielins A–D (1–4), along with two known compounds (5 and 6) have been isolated from a soft coral Cladiella krempfi. The structures of the new metabolites were elucidated by extensive spectroscopic analysis and by comparison with spectroscopic data of related known compounds. Compounds 5 and 6 were shown to exhibit cytotoxicity against a limited panel of cancer cell lines. Furthermore, compounds 2, 3, 5 and 6 were shown to exert significant in vitro anti-inflammatory activity against LPS-stimulated RAW264.7 macrophage cells.